2020
DOI: 10.1126/scitranslmed.aaz5506
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor 3 activates a network of profibrotic signaling pathways to promote fibrosis in systemic sclerosis

Abstract: Aberrant activation of fibroblasts with progressive deposition of extracellular matrix is a key feature of systemic sclerosis (SSc), a prototypical idiopathic fibrotic disease. Here, we demonstrate that the profibrotic cytokine transforming growth factor β selectively up-regulates fibroblast growth factor receptor 3 (FGFR3) and its ligand FGF9 to promote fibroblast activation and tissue fibrosis, leading to a prominent FGFR3 signature in the SSc skin. Transcriptome profiling, in silico analysis and functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 86 publications
0
29
0
Order By: Relevance
“…138 Interestingly, in the skin of patients with systemic sclerosis, only FGFR3B but not FGFR3C was found to be overexpressed. 138 In contrast, in lung fibroblasts exhibiting high expression of FGFR3C, FGF9 revealed antifibrotic effects through downregulation of collagen expression and these effects were partially reversed by FGFR3-knockdown. 86 These findings underscore that differences in isoform expression and the cellular context critically determine FGFR-effects in fibrotic diseases.…”
Section: Fibroblast Growth Factor Receptormentioning
confidence: 97%
See 2 more Smart Citations
“…138 Interestingly, in the skin of patients with systemic sclerosis, only FGFR3B but not FGFR3C was found to be overexpressed. 138 In contrast, in lung fibroblasts exhibiting high expression of FGFR3C, FGF9 revealed antifibrotic effects through downregulation of collagen expression and these effects were partially reversed by FGFR3-knockdown. 86 These findings underscore that differences in isoform expression and the cellular context critically determine FGFR-effects in fibrotic diseases.…”
Section: Fibroblast Growth Factor Receptormentioning
confidence: 97%
“…Although FGFR3 plays an important role in HCC development and progression 9,103,137 and FGFR3 expression is elevated in human cirrhotic livers, 132 the functional role of FGFR3 and its isoforms has not yet been investigated in the context of hepatic fibrosis. A recent study revealed that FGF9‐activated FGFR3 promoted fibrosis in systemic sclerosis through activation of profibrotic signalling pathways 138 . Interestingly, in the skin of patients with systemic sclerosis, only FGFR3B but not FGFR3C was found to be overexpressed 138 .…”
Section: Role Of Fgf‐receptors In Hepatic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, inhibition of PKA by a chemical compound (H89) or specific peptide (PKI 14-22 amide) also increased the yield of iCM reprogramming. We next studied one of the well-known downstream targets of PKA signaling, CREB, which regulates fibroblast [44][45][46][47][48][49] and cardiac function and disease [50][51][52]. We found that CREB inhibitor improves iCM reprogramming and inhibition of p38 signaling, which also regulate the phosphorylation of CREB, consistently enhanced reprogramming efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…FGFR is expressed in fibroblasts and is present in various tissue types, such as skin, cornea, lung, heart, placenta, kidney, and ureter (Hughes, 1997;Root and Shipley, 2000). FGFR has been shown to activate profibrotic signaling pathways in systemic sclerosis (Chakraborty et al, 2020). Nintedanib is an FDA-approved drug used for pulmonary fibrosis and ILD associated with systemic sclerosis (Distler et al, 2019).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%